2011
DOI: 10.1103/physrevb.83.094522
|View full text |Cite
|
Sign up to set email alerts
|

Electron-hole asymmetry in the superconductivity of dopedBaFe2As2seen via the rigid chemical-potential shift in photoemission

Abstract: We have performed a systematic photoemission study of the chemical potential shift as a function of carrier doping in a pnictide system based on BaFe2As2. The experimentally determined chemical potential shift is consistent with the prediction of a rigid band shift picture by renormalized first-principle band calculations. This leads to an electron-hole asymmetry (EHA) in the Fermi surface (FS) nesting condition due to different effective masses for different FS sheets, which can be calculated from the Lindhar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
81
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 33 publications
(30 reference statements)
17
81
1
2
Order By: Relevance
“…Since Co is next to Fe in the atomic periodic table, the primary effects of Co substitution is generally considered to be donation of the extra electron into the FeAs planes. The systematic shift of the Fermi energy observed by ARPES (angle-resolved photoemission spectroscopy) measurements seems to support such a rigid band picture [4][5][6]. Furthermore, the optimum T c of the Ni substituted Ba(Fe 1−x Ni x ) 2 As 2 and Cu substituted Ba(Fe 1−x Cu x ) 2 As 2 requires the doping level, x, to be smaller than the case of Co by a factor of 2∼3 [7][8][9].…”
mentioning
confidence: 80%
“…Since Co is next to Fe in the atomic periodic table, the primary effects of Co substitution is generally considered to be donation of the extra electron into the FeAs planes. The systematic shift of the Fermi energy observed by ARPES (angle-resolved photoemission spectroscopy) measurements seems to support such a rigid band picture [4][5][6]. Furthermore, the optimum T c of the Ni substituted Ba(Fe 1−x Ni x ) 2 As 2 and Cu substituted Ba(Fe 1−x Cu x ) 2 As 2 requires the doping level, x, to be smaller than the case of Co by a factor of 2∼3 [7][8][9].…”
mentioning
confidence: 80%
“…Based on this, it is deduced that the establishment of a proper e value is not a sufficient condition for superconductivity. 27 Moreover, it is found that although Co-122 can be described by the rigid band picture, 10,38 the total extra electron number estimated from the Fermi surface volumes decreases in going from Co-, to Ni-, to Cu-122, described by increasing impurity potential. 39 Most recently, our nuclear magnetic resonance results for Cu-122 attribute the absence of the large superconducting dome in the phase diagram of Cu-122 to the emergence of a nearly magnetically ordered FeAs plane under the presence of orthorhombic distortion.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also point out that with the 3d transition element substitution for Fe, a part of the additional electrons from the transition metal remain localized at the constituents. However, there are several ARPES reports that demonstrate that the Co substitution for Fe donates the charge carriers to the host system according to a rigid band model [19][20][21][22][23]. On the other hand, with the substitution of Ni and Cu for Fe, the additional doping concentration is reduced, while for Zn the additional electrons are completely localized at the Zn ions [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…Many ARPES studies, dealing with the effect of impurities on the electronic structure, are available on weakly correlated 122-type [20][21][22][23]28] and 111-type [29][30][31] iron pnictides. Intriguingly, till now, no ARPES study has been made on the more correlated charge doped 11-type iron chalcogenides, which motivated us for the present study, though there are transport [32][33][34][35], thermal [36], and magnetic measurements [37] reporting on this issue.…”
Section: Introductionmentioning
confidence: 99%